2006
DOI: 10.1177/000313480607201013
|View full text |Cite
|
Sign up to set email alerts
|

Number of Lymph Nodes Examined and its Impact on Colorectal Cancer Staging

Abstract: The status of lymph nodes is the most important prognosticator in colorectal cancer patients. Patients with lymph node involvement have a lower survival rate and are candidates for adjuvant therapy. The purpose of our study was to determine the number of lymph nodes that needs to be examined to accurately detect nodal metastasis. We conducted a retrospective study of 151 patients who underwent colorectal cancer operation at Harbor-UCLA Medical Center. Data from the operative report and pathology report were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…2 Substantial progress in the diagnosis and treatment of CRC has been achieved, but the overall 5-year survival rate of CRC remains low. 3 Although tumor migration and metastasis are known to be the key causes of death in patients with CRC, the molecular pathogenesis of this disease remains largely unclear. Therefore, the identification of biomarkers for CRC would be helpful to predict the metastatic progression and prognosis and to provide a basis for targeted therapy schemes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Substantial progress in the diagnosis and treatment of CRC has been achieved, but the overall 5-year survival rate of CRC remains low. 3 Although tumor migration and metastasis are known to be the key causes of death in patients with CRC, the molecular pathogenesis of this disease remains largely unclear. Therefore, the identification of biomarkers for CRC would be helpful to predict the metastatic progression and prognosis and to provide a basis for targeted therapy schemes.…”
Section: Introductionmentioning
confidence: 99%
“…A minimum of 12 LNs dissected and examined has been recommended as a guideline for colon and rectal cancer surgery for more than a decade 1‐3. Data from various sources have suggested that the dissection of a sufficient number of LNs results in more accurate cancer staging4‐6 as well as improved survival 7‐10. Despite all supporting evidence that evaluating an adequate number of LNs is beneficial for colon cancer patients, data from the Surveillance, Epidemiology, and End Results (SEER) program for the period 1988 to 2001 showed that 63% of patients with locoregional colon cancer had <12 LNs dissected.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of lymph node metastases in colon cancer is the single most important determinant of prognosis after curative resection and significantly impacts whether adjuvant chemotherapy is recommended to a patient. Multiple studies have demonstrated an impressive association between the number of nodes identified in the surgical specimen and cancer‐specific survival; recommendations on the number of nodes that equate to ‘adequacy’ range from 7 to 40 to ‘as many as possible’ [1–9].…”
Section: Introductionmentioning
confidence: 99%